2013
DOI: 10.1097/yic.0b013e3283611cc3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of long-acting injectable risperidone versus oral antipsychotics in the treatment of recent-onset schizophrenia

Abstract: Long-acting injectable antipsychotics may offer a relevant improvement in treatment adherence in recent-onset psychosis, leading to a decreased rate of hospital readmission, a better rate of clinical remission and improved psychosocial adjustment. The aim of the study was to compare the clinical remission rates, number of hospital readmissions and personal and social functioning after 2 years between patients with recent-onset schizophrenia (<2 years) in treatment with risperidone long-acting injectable (RLAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
1
30
0
2
Order By: Relevance
“…However, this practice is not evidence based and there are anecdotal reports that LAIs may be of particular value when used early in the course of illness 16, 23, 26, 27, 28, 29, 30. Recently, a few randomized studies have demonstrated the value of using APs early in the course of schizophrenia 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice is not evidence based and there are anecdotal reports that LAIs may be of particular value when used early in the course of illness 16, 23, 26, 27, 28, 29, 30. Recently, a few randomized studies have demonstrated the value of using APs early in the course of schizophrenia 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, could decrease the likelihood of institutionalization in hospitals and incarceration. Studies comparing long-acting injectable versus oral antipsychotic treatment have provided inconsistent results, [6][7][8][9][10][11][12][13][14][15] with some indication that demonstrating a differential effectiveness among these formulations is better established with a more pragmatic clinical trial design than with one that is more explanatory. [16][17][18][19] With this in mind, we designed the Paliperidone Palmitate Research in Demonstrating Effectiveness (PRIDE) study (ClinicalTrials.gov identifier: NCT01157351) to compare once-monthly paliperidone palmitate and daily oral antipsychotics in real-world schizophrenia, as defined by subject inclusion criteria, treatment, and outcomes.…”
Section: Rationalementioning
confidence: 99%
“…Risperidone long‐acting injection (RLAI) is the first of its kind for second‐generation antipsychotics. Previous studies examining the safety and efficacy of risperidone in treating patients with schizophrenia included case–control studies, randomized‐controlled trials, and observational studies . In the case–control studies and randomized‐controlled trials, the patients were selected and grouped before being enrolled in the studies.…”
mentioning
confidence: 99%
“…Previous studies examining the safety and efficacy of risperidone in treating patients with schizophrenia included case-control studies, randomizedcontrolled trials, and observational studies. [19][20][21][22][23][24][25][26][27] In the case-control studies and randomized-controlled trials, the patients were selected and grouped before being enrolled in the studies. Although these are the studies with the highest methodological quality, they may also have a lower external validity.…”
mentioning
confidence: 99%